Development of metal-supported solid oxide fuel cells with a thin-film electrolyte under an oxidizing atmosphere - Jaeseok Lee; Sungmin Kang; Heedae Lee; Kunho Lee; Gwangwoo Han; Sanghun Lee; Dong-Hyun Peck; Joongmyeon Bae (Journal of Power Sources Advances)
Metal-supported solid oxide fuel cells (SOFCs), which have received much attention based on their high thermo-mechanical strength, are generally fabricated under a reducing atmosphere to prevent oxidation of the metal. The fabrication of metal-supported SOFCs under an oxidizing atmosphere resolves certain inherent issues related to fabrication in a reducing atmosphere, such as instability of the cathode materials and the inter-diffusion phenomenon. On the other hand, this approach limits the process temperature to prevent the excessive oxidation of the metal. In this work, a means by which to fabricate metal-supported SOFCs under an air environment is developed with a thin-film electrolyte, with deposition at room temperature. By introducing a pore-reducing layer while also controlling the viscosity of the coating solution, the surface of the anode is designed to be dense and flat, enabling the stable deposition of a dense thin-film electrolyte. Notable electrochemical performance is exhibited considering the limited process temperature, which must remain below 1000 °C. Through a durability test including temperature cycling and a post-mortem analysis, remarkable robustness of the metal-supported SOFCs is observed.